2020
DOI: 10.1111/ecc.13264
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the “Shared Community Follow‐up” after a germ cell tumour—A novel initiative for remote cancer follow‐up enhanced by online patient‐reported outcome measures

Abstract: The aim of cancer follow-up is to detect relapses early, to monitor and manage early and late treatment toxicities, and to offer holistic post-treatment support (Heathcote et al., 2018). As more people live beyond cancer, the demand for follow-up monitoring increases (Maddams, Utley, & Møller, 2012; Stark et al., 2015). The problem is that cancer services will be unable to cater for the projected 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Views about ePRO follow‐up were mixed among patients, and it may not be suitable for all patients. This finding is similar to other studies where patients are offered a choice (Lindner et al, 2020 ; Morrison et al, 2018 ; Qaderi et al, 2021 ). Feelings of abandonment were raised by some, which is common at treatment completion even within face‐to‐face follow‐up (Lydon et al, 2009 ), and is cited in a narrative review of the impact of telehealth interventions (Cox et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Views about ePRO follow‐up were mixed among patients, and it may not be suitable for all patients. This finding is similar to other studies where patients are offered a choice (Lindner et al, 2020 ; Morrison et al, 2018 ; Qaderi et al, 2021 ). Feelings of abandonment were raised by some, which is common at treatment completion even within face‐to‐face follow‐up (Lydon et al, 2009 ), and is cited in a narrative review of the impact of telehealth interventions (Cox et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…This finding is similar to other studies where patients are offered a choice (Lindner et al, 2020;Morrison et al, 2018;Qaderi et al, 2021).…”
Section: Effective Questions and Data Monitoringsupporting
confidence: 91%
See 1 more Smart Citation
“…An ePRO follow-up pathway enables patient’s symptoms/needs to be monitored regularly, remotely, and communicated with their clinicians, and prompt face-to-face review when symptoms/concerns are reported. ePRO follow-up services are emerging in the literature [ 22 , 26 28 ]. Qualitative interview work conducted in 2018 illustrated that ovarian cancer clinicians and patients were supportive of an ePRO pathway model post-treatment, suggesting the benefits would be reduced hospital visits when well, regaining normality, but continued access to service/clinicians for reassurance when required [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women who had cancer that was more complex (e.g. non-secretors of CA125) [37], had other comorbidities, or low technology/computer con dence, were less likely to feel con dent and reassured on ePRO follow-up. Furthermore, despite attempts, none of the women who withdrew were interviewed, therefore likely missing some negative experiences.…”
Section: Discussionmentioning
confidence: 99%